Disability and costs of IHD attributable to the consumption of trans-fatty acids in Brazil - Magda do Carmo Parajára; Aline Siqueira Fogal Vegi; Ísis Eloah Machado; Mariana Carvalho de Menezes; Eliseu Verly-Jr; Adriana Lúcia Meireles (Cambridge University Press, 2024)
Abstract Objective: To estimate the disability and costs of the Brazilian Unified Health System for IHD attributable to trans-fatty acid (TFA) consumption in 2019. Design: This ecological study used secondary data from the Global Burden of Disease (GBD) Study 2019 to estimate the years lived with disability from IHD attributable to TFA in Brazil in 2019. Data on direct costs (purchasing power parity: 1 Int$ = R$ 2·280) were obtained from the Hospital and Ambulatory Information Systems of the Brazilian Unified Health System. Moreover, the total costs in each state were divided by the resident population in 2019 and multiplied by 10 000 inhabitants. The relationship between the socio-demographic index, disease and economic burden was investigated. Setting: Brazil and its twenty-seven states. Participants: Adults aged ≥ 25 years of both sexes. Results: IHD attributable to TFA consumption resulted in 11 165 years lived with disability (95 % uncertainty interval 932-18 462) in 2019 in Brazil. A total of Int$ 54 546 227 (95 % uncertainty interval 4 505 792-85 561 810) was spent in the Brazilian Unified Health System in 2019 due to IHD attributable to TFA, with the highest costs of hospitalisations, for males and individuals aged ≥ 50 years or over. The highest costs were observed in Sergipe (Int$ 6508/10 000; 95 % uncertainty interval 576-10 265), followed by the two states from the South. Overall, as the socio-demographic index increases, expenditures increase. Conclusions: TFA consumption results in a high disease and economic IHD burden in Brazil, reinforcing the need for more effective health policies, such as industrial TFA elimination, following the international agenda.